The Effect Of Service Quality On Satisfaction And Behavioral Intention In Flight Services Pt. Sea Lion. - Rama, Maria de la Cruz del Río; Salzberger, Thomas (Journal of Management, 2022)
Study The following goals are pursued: (1) To understand and analyze the relationship between service quality and behavioral intention in the company flight services provided by PT. Lion Air; (2) To determine and assess the impact of service quality on customer satisfaction at said company; and (3) To understand and analyze the relationship between satisfaction and behavioral intention in said company. Study This feature explanation tries to explain the positions of the variables under study as well as the connections and interactions between them. The target demographic for the study is Lion Air passengers, and the research location is the Office of PT. Lion Air Surabaya at Juanda Airport. populace under study This is a list of all passengers on board flight PT. Lion Air that number No known (unlimited) and cannot be specifically named (infinitive). The Equation Model Structure (also known as the Structured Equation Model or SEMS) is the tool analysis employed. According to research findings, service quality significantly influences behavioral intentions, satisfaction significantly influences behavioral intentions, and service quality significantly influences behavioral intentions.